POLLEN GRAINS OF THE GENUS CLADAITINA EXTRACTED FROM THE GUT OF THE EARLY PERMIAN INSECT TILLYARDEMBIA (GRYLLOBLATTIDA) - Afonin S.A. (My University, 2000)
The sporoderm morphology and ultrastructure of pollen grains extracted from the gut of the Early Permian insect Tillyardembia antennaeplana G. Zalessky (Grylloblattida) are studied using light and electron microscopes. The assignment of these pollen grains to the formal genus Cladaitina Maheshwari et Meyen, which includes pollen from the microsporoclade Cladostrobus (Rufloriaceae), is established. For the first time the sporoderm ultrastructure of Cladaitina is studied, and the significance of this type of pollen for the feeding of Grylloblattida is revealed.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская